Exercise as a Useful Intervention to Reduce Alcohol Consumption and Improve Physical Fitness in Individuals With Alcohol Use Disorder: A Systematic Review and Meta-Analysis - Lardier, David T.; Coakley, Kathryn E.; Holladay, Kelley R.; Amorim, Fabiano T.; Zuhl, Micah N. (Frontiers in Psychology, 2021)
Objective: This meta-analysis and systematic review examined the effects of exercise interventions on alcohol consumption and binge drinking in individuals with alcohol use disorder (AUD). Data sources: PubMed, Web of Science, Google Scholar, SPORTDiscus, and ERIC databases. Study Inclusion and Exclusion Criteria: Peer-reviewed randomized controlled trials published in English between 1970 and 2021. All studies compared exercise (Ex) and treatment as usual (TAU) to TAU in adults with an alcohol-related diagnosis. All forms of exercise interventions were included (e.g., aerobic exercise, yoga, resistance exercise, etc.). Data Extraction: Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols standard and the Meta-Analyses and Systematic Reviews of Observational Studies guidelines were followed. Risk of bias was assessed using the Cochrane risk-of-bias tool as described by the Cochrane Handbook for Systematic Reviews and Interventions. Results: The literature searches retrieved a combined 2527 studies, with 1,034 studies screened after removal of duplicates and 973 (94%) rejected after reviewing titles and abstracts. Full-text review was performed on 61 studies, with seven studies meeting inclusion criteria for qualitative and meta-analysis. Across seven studies (n = 492 participants), a significant effect (Z-value = −3.37; g = −0.30; 95% CI [−0.50—−0.09]; p = 0.001) was found for Ex+TAU on drinking volume. There was no effect of Ex+TAU on binge drinking. The effect of Ex+TAU on physical fitness (VO2max, ml•kg−1•min−1) was significant (Z-score = 3.70; g = 0.64; 95% CI [0.19–1.08]; p < 0.001). Conclusions: Exercise interventions may decrease alcohol consumption and improve fitness and can be an effective adjunctive treatment for individuals with alcohol-related diagnoses including AUD.